2015
DOI: 10.1007/s00018-014-1813-y
|View full text |Cite
|
Sign up to set email alerts
|

The secret life of a megakaryocyte: emerging roles in bone marrow homeostasis control

Abstract: SUMMARY Megakaryocytes are rare cells found in the bone marrow, responsible for the everyday production and release of millions of platelets into the bloodstream. Since the discovery and cloning, in 1994, of their principal humoral factor, thrombopoietin, and its receptor c-Mpl, many efforts have been directed to define the mechanisms underlying an efficient platelet production. However, more recently different studies have pointed out new roles for megakaryocytes as regulators of bone marrow homeostasis and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 232 publications
(246 reference statements)
0
56
0
2
Order By: Relevance
“…MKs secrete a broad array of cytokines to regulate hematopoiesis. 46 To begin to understand the MK signals responsible for E-SLAM expansion in Pf4/FF1 mice, we measured the expression levels of FGF1 , Pf4 , Transforming growth factor beta 1 ( TGFb-1 ), Chemokine (C-X-C motif) ligand 12 ( CXCL12 ), VEGFa , chemokine (C-X-C motif) receptor 4 ( CXCR4 ) in Pf4/FF1 ( n = 4) and control MKs ( n = 3) using quantitative PCR (qPCR). We confirmed that there was upregulation of FGF1 (twofold, P = 0.004) in Pf4/FF1 MKs compared with control MKs (Figure 6c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MKs secrete a broad array of cytokines to regulate hematopoiesis. 46 To begin to understand the MK signals responsible for E-SLAM expansion in Pf4/FF1 mice, we measured the expression levels of FGF1 , Pf4 , Transforming growth factor beta 1 ( TGFb-1 ), Chemokine (C-X-C motif) ligand 12 ( CXCL12 ), VEGFa , chemokine (C-X-C motif) receptor 4 ( CXCR4 ) in Pf4/FF1 ( n = 4) and control MKs ( n = 3) using quantitative PCR (qPCR). We confirmed that there was upregulation of FGF1 (twofold, P = 0.004) in Pf4/FF1 MKs compared with control MKs (Figure 6c).…”
Section: Resultsmentioning
confidence: 99%
“…1923,46,55,56 To investigate how JAK2 V617F -mutant MKs affect E-SLAM cell numbers and function, we performed a series of experiments. Although there was upregulation of FGF1, which positively expand MKs and facilitate HSPC expansion during stress hematopoiesis, in Pf4/FF1 MKs compared with control MKs, Pf4/FF1 MKCM suppressed E-SLAM cell proliferation in vitro , suggesting that the sum of the MK humoral influences is not responsible for the expansion of E-SLAM cells witnessed in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we showed that TPO is a pivotal regulator of this function by inducing TGF-β1 release, thus controlling ECM component synthesis in an autocrine manner. TGF-β1, as well as other soluble factors (e.g., ADP, VEGF, PF4) and ECM components (e.g., vWF, fibronectin), have been shown to be constitutively released by megakaryocytes to regulate their own differentiation and proplatelet formation [134,136,142,143,144,145,146], indicating that in physiological conditions megakaryocytes can activate an autocrine/paracrine loop which contribute to both their own development and overall bone marrow homeostasis [147]. Consistently, impaired synthesis and release of these proteins has been linked to altered megakaryocyte maturation, proplatelet formation and/or ECMs production [141,142,143,148], leading to a broad spectrum of clinical outcomes, from defective peripheral blood platelet count to deregulated bone marrow homeostasis [147,149,150].…”
Section: Thrombopoiesis: the Long Route Of Megakaryocytes To Platementioning
confidence: 99%
“…1,2 The failure of HSCs to guarantee the physiologic homeostasis of one or more progenitors for circulating blood cells leads to pathologic conditions, such as aplastic anemia (AA) or myelodysplastic syndromes (MDS), characterized by peripheral pancytopenia of heterogeneous severity. 3,4 A selective cytopenia of blood platelets, namely thrombocytopenia, may occur because of mutations in genes relevant for the functions of maturing megakaryocytic progenitors, as in inherited thrombocytopenias (IT).…”
Section: Introductionmentioning
confidence: 99%